(untitled) (Journal of Philosophy Culture and Political Science, 2022)
The article examines the methods used in contemporary epistemology, we will focus on ontologically based epistemology made by Hartmann and Heidegger. The traditional philosophy which is under big critics should be re-examined and given its original meaning by giving it a new direction. The article is not about how Hartmann and Heidegger were doing it, but it rather about why it is necessary to switch to an ontology structure instead of the main search of traditional philosophy. Mainly it sprouted in the XIX century and took its true form in the XX century. The positivist understanding of science, in the XIX century, argued that science and philosophy had great responsibilities in changing and transforming the world, and accordingly, it reduced philosophy to a discipline based solely on natural sciences, logic and mathematics. According to this understanding, western-based concepts such as ’universality’, ’objectivity’, and ’rationality’ were glorified as indispensable values of modern science. However, since XX century the positivist understanding has been subjected to serious criticism. One of these general transformations is that Heidegger and Hartmann tried to reconstruct the way of thinking in the search for the absolute in traditional philosophy. Key words: Epistemology, ontology, method, positivism, objectivity, Hartmann, Heidegger.